MORPHOLOGICAL CHANGES IN THE LIVER OF OFFSPRING BORN TO MOTHERS IN A STATE OF EXPERIMENTAL STRESS - Nortaeva N.A.,; Abdudjalilova Y.H.,; Raxmonberdiyev M.A., (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Annotation: The article scientists who have studied the effect of stress on the structure and  function of the liver have conducted a number of studies. Stress is a universal naspecific neurogormonal reaction of the body in the form of an injury that manifests itself with increased body resistance, or a voltage of non-specific adaptation mechanisms in response to a signal that threatens the life or well-being of the body.